Current paradigms in epigenetic anticancer therapeutics and future challenges. (August 2022) - Singh, Manoj; Kumar, Vikas; Sehrawat, Nirmala; Yadav, Mukesh; Chaudhary, Mayank; Upadhyay, Sushil K.; Kumar, Sunil; Sharma, Varruchi; Kumar, Sandeep; Dilbaghi, Neeraj; Sharma, Anil K.
Abstract: Any alteration at the genetic or epigenetic level, may result in multiplex of diseases including tumorigenesis which ultimately results in the cancer development. Restoration of the normal epigenome by reversing the epigenetic alterations have been reported in tumors paving the way for development of an effective epigenetic treatment in cancer. However, delineating various epigenetic events has been a challenging task so far despite substantial progress in understanding DNA methylation and histone modifications during transcription of genes. Many inhibitors in the form of epigenetic drugs mostly targeting chromatin and histone modifying enzymes including DNA methyltransferase (DNMT) enzyme inhibitors and a histone deacetylases (HDACs) inhibitor, have been in use subsequent to the approval by FDA for cancer treatment. Similarly, other inhibitory drugs, such as FK228, suberoylanilide hydroxamic acid (SAHA) and MS-275, have been successfully tested in clinical studies. Despite all these advancements, still we see a hazy view as far as a promising epigenetic anticancer therapy is concerned. The challenges are to have more specific and effective inhibitors with negligible side effects. Moreover, the alterations seen in tumors are not well understood for which one has to gain deeper insight into the tumor pathology as well. Current review focusses on such epigenetic alterations occurring in cancer and the effective strategies to utilize such alterations for potential therapeutic use and treatment in cancer.